'Just a life' : a feminist posthuman reading, thinking and hearing practice with displaced women’s struggles and transformation : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University, Manawatū, New Zealand - Kramnaimuang King, Dolruedee (Massey University, 2025)
The lived stories of displaced English-language schoolmate peers inspired me to read and interrogate the literature on trauma, particularly in relation to trauma-informed mental health disorders and interventions. Through a critical, posthumanist feminist approach, I explored how the process of knowledge production in relation to social power relations and responsibility is conceptualised. I found that the current ontological-epistemological process reflects a dominant, dualistic, Eurocentric approach with universal pretensions that circumscribes the meaningful figuration of subject, trauma and transformation. This problem of framing prompted my initial research question: What women’s struggle and transformation assemblages might exist in relation to women’s situated-embodied-embedded experiences and contexts? I conversed with five displaced women, also sharing photos and recollections. A posthuman relational ethics was enacted including a reflexive hearing practice to advance understandings of subject, trauma, and transformation. This practice, including Braidotti’s (2010) ‘by heart and by memory’, and continued engagement with literature and theory, evolved throughout the research process, shifting my research question to: How do displaced women experience and transform their situated struggles through both relational disruptions and capacities and what relational contexts are involved? In effect, I was enabled to hear displaced women’s stories differently, as we made meaning together. Hearing their stories encouraged me to shift away from normative-stereotypical understanding towards multiple-dynamic ways of knowing through the process of becoming. Through our discussion and my analysis, we co-created knowledge that shifted us from ‘assumed’ trauma associated with victimised subjects to engagement with the Deleuzian (1997) concept of ‘just a life’. The displaced women affirmed that they were positioned as less than human at times throughout their journeys, within the complexities of their multi constituent lived experiences associated with gender, history, religion, culture, context, their categorisation and subsequent treatment as ‘refugees’. Their gifted stories challenged the normalisation of trauma discourse and suggested that as subjects, they were multiple, relational and embraced change through more than human, interdependent relations, involving everyday negotiation and resistance. Their ongoing lived stories and experiences present different ontologies, knowledges and practices which substantively, ethically and politically confront and potentially help address imbalance in social power and justice.
Figures 3, 6 and 8 are reproduced with permission.
Keywords: 470211 Migrant cultural studies; 440505 Intersectional studies; 520304 Health psychology